2009
DOI: 10.5704/moj.0905.002
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of Intra-Articular Injection of Hyaluronic Acid in the Treatment of Knee Osteoarthritis

Abstract: This study was conducted to evaluate the efficacy of intraarticular injection of hyaluronic acid for the treatment of knee osteoarthritis. Patients with knee osteoarthritis were followed for a period of six months to assess the efficacy of intra-articular injection of hyaluronic acid given three times in three consecutive weeks. Fifty patients were reviewed at two, eight and 24 weeks post-injection. The average age was 60.9 years and female to male ratio was 3:1. Patients were assessed using the Lequesne Algof… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 8 publications
(5 reference statements)
0
7
0
1
Order By: Relevance
“…In our study, high molecular weight (HMW) HA was chosen instead of low molecular weight (LMW) HA mainly because the HMW HA (1.5x 10 6 Daltons) closely resembles the molecular weight of endogenous HA (~2 x106 Daltons) in the extracellular matrix 27 , 28 , 30 . Studies have demonstrated that HMW HA down regulates the gene expression of osteoarthritis associated cytokines and enzymes in fibroblast like synoviocytes (FLS) 14 , 15 , 29 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In our study, high molecular weight (HMW) HA was chosen instead of low molecular weight (LMW) HA mainly because the HMW HA (1.5x 10 6 Daltons) closely resembles the molecular weight of endogenous HA (~2 x106 Daltons) in the extracellular matrix 27 , 28 , 30 . Studies have demonstrated that HMW HA down regulates the gene expression of osteoarthritis associated cytokines and enzymes in fibroblast like synoviocytes (FLS) 14 , 15 , 29 .…”
Section: Discussionmentioning
confidence: 99%
“…We have standardized patient selection by only including patients who had received specific HA and PRP concentration or preparation method. All patients included in the study had received 4 ml high molecular weight (1.476 x 10 6 average Daltons) hyaluronic acid with concentration of 22mg/ml. HMW HA was specifically selected because many earlier studies showed greater and longer efficacy in reducing pain and other symptoms and recovering articular function as compared to LMW HA 25 , 26 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Patients with knee OA may receive electrotherapy, [5,6] joint mobilization, [7] therapeutic exercises, [8] virtual reality-based therapy, [9] or intra-articular injection of hyaluronic acid [10] to reduce pain and/or to improve functional ability. However, total knee arthroplasty (TKA) is recommended as an intervention for managing severe knee OA [11] or when the conservative treatments have failed.…”
Section: Introductionmentioning
confidence: 99%
“…5,7,9 In literature, several intraarticular injections of hyaluronan are recommended to provide a control for OA progression; but it is not known whether there is a need for repeated injections and if so, what is the ideal time between injections. 6,12 Biodegradable polymers are the most widely preferred systems in controlled release applications. 5,10,11 So, this approach has limitations including short term pain relief and requirement of frequent injections.…”
Section: Introductionmentioning
confidence: 99%